Investment Risk Management Strategies in the Sharia Capital Market: Perspectives of Retail and Institutional Investors - Sisca Debyola Widuhung; Yatimin; Metha Dwi Apriyanti; Luqman Hakim; Andry Priharta (LP2M IAIN Palopo, 2025)
.